Using discrete event visual simulation to teach process modelling in MBA operations management courses. (10th April 2015) - Taj, Shahram; Mousavidin, Elham
We discuss our experience using discrete event visual simulation to teach MBA students process modelling/analysis as part of a required operations management/supply chain class. We apply a hybrid approach by using a combination of simulation and such process mapping/analysis tools as flow–diagram, capacity/utilisation, and Little's law to real world processes. We link improvements in operational performance indicators to financial performances. Our approach provides future managers with a deep understanding of the conceptual and practical aspects of process modelling/analysis, emphasising the complexities involved in real life dynamic and stochastic processes. We also developed a framework for assessing experiential learning using this teaching approach. The use of the discrete event visual simulation approach in operation management classes is novel and highly valuable. It is novel because we offer a four–week module in a 15–week class versus courses that exclusively teach simulation, and it is valuable in rendering simulation modelling accessible to a broader audience.